Beyond the Climate: Multiple Sources of Risk in Agriculture in the United States, Brazil and Argentina - Cabrini, Silvina María; Colussi, Joana; Schnitkey, Gary; Irwin, Scott (Universidad de Illinois, 2025)
This report presents the results of a survey on farmers’ perceptions in the U.S. Midwest, the Argentine Pampas, and southern Brazil regarding the main sources of risk facing their businesses. Conducted in 2022 and 2023, the survey included 475 crop producers from the United States (137), Argentina (158), and Brazil (180), the main grain production areas in the world. Farmers across all three regions identified multiple sources of business risk, with significant differences observed among the countries in the frequency of selected risk sources.